Integrating health promotion into occupational health surveillance: The Italian approach and beyond - Nicola MAGNAVITA; Igor MERAGLIA (GIornale Italiano di Psicologia e Medicina del Lavoro, 2024)
Health surveillance in the workplace increasingly integrates health promotion activities alongside traditional occupational risk prevention. The Italian National Prevention Plan (PNP) encourages companies and occupational physicians to adopt health promotion strategies, inspired by the “Total Worker Health” (TWH) model developed by NIOSH in the United States. However, this study highlights the limitations of directly applying the TWH model in Italy without significant adaptations, due to differences in healthcare systems, company structures, and economic contexts. Over the past 15 years, Italian occupational physicians have developed and implemented health promotion models that are integrated into routine surveillance activities, addressing various aspects of workplace health and well-being. These programs, which go beyond the US TWH model, can be executed at no cost to companies and with minimal additional effort from occupational physicians. University researchers play a central role in designing these initiatives, analyzing data, and disseminating results, making these resources freely accessible to interested professionals.